What determines psychological well-being among Iranian female adolescents? Perceived stress may overshadow all determinants - Haleh Heizomi; Haidar Nadrian (Tabriz University of Medical Sciences, 2018)
Background: Mental health problems, as one of the most neglected issues among adolescents,are common during adolescence and emerging adulthood. The aim of present study was to investigate the determinants of psychological well being among female adolescents in Tabriz,Iran.Methods: In this cross-sectional study, multi-stage cluster sampling was employed to recruit 289 female high school students to participate in the study during 2013-2014. A 3-section questionnaire was applied to collect data. Hierarchical linear regression analysis was applied to illustrate the variations in psychological wellbeing score on the basis of socio-demographic and psychological variables.Results: Self-efficacy, hopefulness, happiness and life satisfaction were positively correlated (r> 0.400) and perceived stress was negatively associated with psychological well-being (r =-0.689). In the first model, satisfaction with family lifestyle (β = 0.168, P < 0.001) and perceived stress (β = -0.470, P < 0.001) were the most significant positive and negative predictors for psychological wellbeing, respectively (R2 = 0.595, P < 0.001). In the second model (step 6),physical activity (β = -0.109, P < 0.019), have/had boyfriend (β = 0.237, P < 0.001), hopefulness(β = -0.130, P < 0.05) and happiness (-β = 0.387, P < 0.001) were significant predictors for perceived stress (R2 = 0.453, P < 0.001).Conclusion: Considering the various behavioral, mental and social predictors of psychological wellbeing, it seems that perceived stress has overshadowed the influence of a majority of the other factors. Such influence may be due to the specific cultural and context-based rules enforced for female adolescents in the Iranian community.